The Micromechanical Signature of Pituitary Adenomas: New Perspectives for the Diagnosis and Surgery. Issue 9 (3rd July 2021) - Meyer, Mikaël; Bouchonville, Nicolas; Gaude, Christophe; Gay, Emmanuel; Ratel, David; Nicolas, Alice
Abstract : Pituitary adenomas are common tumors in the skull base that are associated with significant morbidity due to local compressive effects, hormonal hypersecretion, or treatment‐associated endocrine deficiency. Pituitary adenomas are often surgically resected to improve clinical symptoms, with the help of magnetic resonance imaging (MRI) to locate the tumor tissues. But still a large proportion of adenoma fail being located, being either too small or not dense enough. In addition, normal and tumor tissues do not always show optical contrast in endoscopic endonasal trans‐sphenoidal surgery. Finding new markers to delineate the tumor tissue has become mandatory to help the surgical procedure and limit relapses. Herein, an indentation‐type atomic force microscope is used to show that tumor tissues are two orders of magnitude softer than normal tissues, independent of the type of hormonal secretion. This softening correlates with the degradation of the reticulin, type IV collagen, and laminin scaffolds in all the tumors. This significant difference suggests that intraoperative lesion localization and margin assessment could be evaluated by an approach based on stiffness measurement. Abstract : Despite the help of magnetic resonance imaging, many pituitary adenomas fail being located, being either too small or not dense enough. Stiffness measurement using atomic force microscopy shows that tumor tissues are two orders of magnitude softer than normal tissues, independent of the hormonal secretion type. This observation opens perspectives for the development of surgery assistance based on stiffness measurements.